Single-center experience demonstrating low adverse events and high efficacy with self-expandable metal esophageal and biliary stents for pseudocyst and walled off necrosis drainage - Ortizo, Ronald Dungca; Jalali, Farid; Thieu, Daniel; Yu, Allen; Bucayu, Robert; Paiji, Christopher; Fortinsky, Kyle; Chang, Kenneth; Lee, John Gunn; Samarasena, Jason Buddika (Endoscopy International Open, 2020)
Background and study aims Lumen-apposing metal stents (LAMS) have been designed as proprietary stents for the management of pseudocysts (PC)/walled off necrosis (WON). There has been concern about adverse events (AEs) with LAMS including bleeding, buried stent syndrome and migration. Prior to LAMS becoming available, fully-covered self-expandable metal esophageal and biliary stents (FCSEMSs) were used off-label for management of PC/WON with many centers demonstrating low rates of AEs. The primary aim of this study was to study the safety and efficacy of FCSEMS for the management of pseudocysts/WON.Patients and methods This was a retrospective review of all endoscopic ultrasound (EUS)-guided placement of FCSEMSs for drainage of PC/WON cases performed at our institution over 4-year period. The primary outcomes studied were technical success, AEs, PC/WON resolution, and salvage surgical/radiologic intervention.Results Technical success achieved in 65 of 65 (100 %) study patients. An AE occurred 0 of 25 patients (0 %) with PC, and in 10 of 40 patients (25 %) with WON: bleeding (3 %), migration (5 %) and stent dysfunction/infection (18 %). There was resolution in 25 of 25 patients (100 %) with a PC and 31 of 40 patients (78 %) with a WON. Salvage therapy by interventional radiology or surgery was performed in nine of 40 patients (22 %).Conclusions This single-center 4-year experience in the pre-LAMS era showed that FCSEMS was safe and effective in all patients with PC and over 75 % of patients with WON. Given the large cost differential between LAMS and FCSEMS and the efficacy and safety shown with FCSEMS, we believe that FCSEMS should still be considered a first-line option for patients with pancreatic fluid collections, particularly in patients with PCs.